Testing of the suggested algorithm for the correction of psychoemotional stress manifestations in students through the use of meditative techniques in combination with pharmacological support in the jujutsu martial art - Orlov, Oleksandr Ivanovych; Gunina, Larysa Mykhailivna (Литовська олімпійська академія, 2024)
The relevance of studying the mental health of students and the development of methods for the correction of emerging pathological conditions is determined, first of all, by the presence of stress-inducing factors in the student environment such as test-taking situations, periods of social adaptation, the need for professional self-determination, etc., which is complemented by social tension in the world and the deterioration of the ecological environment. Unfortunately, the lack of timely assistance can have profound negative consequences for the physical health and life quality of the future generation, which necessitates additional measures to preserve the psychoemotional state of university students. It is known that in European and American culture the solution of psychoemotional state disorders has been realized long enough ago by borrowing Eastern mental practices with their subsequent adaptation to the socio-cultural values of mankind: Tibetan Buddhist meditation, meditative neurobiology, anti-stress meditations, etc. However, it has never been discussed that such practices can be supplemented with measures based on the achievements of modern pharmacology and nutritional and metabolic support. Therefore, the authors set the goal to substantiate and experimentally test the effectiveness of the combined meditative-pharmacological methodology of mitigating the emotional tension manifestations in students of higher educational institutions in the course of classes in the jujutsu martial art. The paper analyzes modern scientific and scientific-methodological literature and studies the factors influencing the mental health of students, in particular, the intensity of psychoemotional stress manifestations during study in higher education institutions. The negative impact of this phenomenon on the functional state of organs and systems of the body with deterioration of health and life quality is proved. The expediency of using meditative techniques to reduce the intensity of stress manifestations is shown. For the first time in the practice of martial arts, the combination of meditation during the training process of students engaged in the jujutsu martial art to reduce the intensity of stress manifestations and the «Acetyl-L-carnitine» special neuroprotective nutritional supplement to correct the emotional stress manifestations in students of higher education institutions has been used. Thus, to reduce the stress manifestations students tend to use means that not only fail to prevent mental health but even often produce a negative impact on it (nicotine, alcohol, drugs, physical and mental overload, etc.). The use of meditative techniques for this purpose in combination with special neuroprotective means largely solves the issue of reducing the intensity of psychoemotional stress manifestations in students of higher education institutions.

Актуальність вивчення психічного здоров'я студентів та розробки методів корекції виникаючих патологічних станів визначається, насамперед, наявністю стресогенних факторів у середовищі студентів, таких як ситуації складання іспитів, періоди соціальної адаптації, необхідність професійного самовизначення тощо, що доповнюється соціальним напруженням у світі та погіршенням екологічного середовища. На жаль, відсутність своєчасної допомоги може мати глибокі негативні наслідки для фізичного здоров'я та якості життя майбутнього покоління, що вимагає додаткових заходів для збереження психоемоційного стану студентів університетів. Відомо, що в європейській та американській культурі рішення проблем психоемоційного стану було реалізовано досить давно шляхом запозичення східних психічних практик з їх наступною адаптацією до соціокультурних цінностей людства. Тибетська буддійська медитація, медитативна нейробіологія, антистресові медитації тощо. Однак ніколи не обговорювалося, що такі практики можуть бути доповнені заходами, що ґрунтуються на досягненнях сучасної фармакології та харчової і метаболічної підтримки. Тому автори поставили мету обґрунтувати та експериментально перевірити ефективність комплексу медитативно-фармакологічної методики зменшення проявів емоційної напруги у студентів вищих освітніх закладів під час занять бойовим мистецтвом джиу-джитсу. У статті аналізується сучасна наукова та науково-методологічна література і вивчаються фактори, що впливають на психічне здоров'я студентів, зокрема інтенсивність проявів психоемоційного стресу під час навчання у вищих навчальних закладах. Доведено негативний вплив цього явища на функціональний стан органів і систем організму з погіршенням здоров'я та якості життя.
Keywords: student youth; psychoemotional stress; meditation; martial arts; jujutsu; mental health; neuroprotectors; студентська молодь; психоемоційний стрес; медитація; бойові мистецтва; джиу-джитсу; психічне здоров'я; нейропротектори